Dutch version of the Victorian Institute of Sports Assessment-Achilles questionnaire for Achilles tendinopathy: Reliability, validity and applicability to non-athletes - Sierevelt, Inger (World J Orthop, 2018)
AIM: To translate the Victorian Institute of Sports Assessment-Achilles (VISA-A) questionnaire into the Dutch language (VISA-A-NL), and to assess its reliability, validity, and applicability to non-athletes. METHODS: After translation according to a forward-backward protocol, 101 patients with complaints of Achilles tendinopathy were asked to fill out the VISA-A-NL at two time points together with visual analogue scale, the Foot and Ankle Outcome Score, and the Short Form-36 questionnaires. Reliability, internal consistency, construct validity, and content validity were tested. RESULTS: The VISA-A-NL showed high reliability (0.97, 95%CI: 0.95-0.98). Cronbach’s alpha (internal consistency) was 0.80. It increased to 0.88 without activity domain. Correlation with other questionnaires was moderate or poorer. CONCLUSION: The VISA-A-NL proved to be an excellent evaluation instrument for the Dutch physician. If applied to non-athletes, using a modified score (questions 1-6) should be considered.